Effects of Polyphenol-Rich Foods on Human Health - Giuseppe Grosso (Ed.) (MDPI - Multidisciplinary Digital Publishing Institute, 2018)
Over the last few years, polyphenol has received a great deal of attention due to their potential beneficial effects on human health. Widely contained in foods commonly consumed in all populations worldwide, polyphenols represent an attractive explanation of the beneficial effects, not only of fruits and vegetables, characteristic components of healthy dietary patterns, but also of other plant-derived foods, such as tea, coffee, and cocoa, which only recently have been exploited as being beneficial for humans. In addition to the numerous biological properties, polyphenols have been indicated as being responsible for a decreased risk of metabolic disorders, cardiovascular disease, and certain cancers. The book addresses original research and reviews of literature concerning polyphenol-rich foods and human health.